Socio-economic status and academic achievement trajectories from childhood to adolescence - Caro, D; McDonald, J; Douglas Willms, J (2009)
Although a positive relationship between socio-economic status and academic achievement is well-established, how it varies with age is not. This article uses four data points from Canada's National Longitudinal Study of Children and Youth (NLSCY) to examine how the academic achievement gap attributed to SES changes from childhood to adolescence (ages 7 to 15). Estimates of panel data and hierarchical linear models indicate that the gap remains fairly stable from the age of 7 to 11 years and widens at an increasing rate from the age of 11 to the age of 15 years. Theoretical arguments and policy implications surrounding this finding are discussed. ©2009 Société canadienne pour l'étude de l'éducation/Canadian Society for the Study of Education.